Capturing the moment: developing a reflective narrative tool for training in the education professions. Issue 2 (3rd July 2018) - Ben-Asher, Smadar; Roskin, Nitza
ABSTRACT: The study presents a reflective tool that enables students to observe their personal and professional development process by formulating personal life stories; these narratives serve to identify each student's characteristic lifestyle and modes of action. An atypical event is 'captured', one containing an 'I-moment' with a 'different' kernel of insight or action. The tool proposes reflective examination of the event, critical observation, re-conceptualization, and new action. This approach can expand current training methods, serving as a means for students in education professions both to analyze their own self-development and to assist others in resolving difficulties and overcoming barriers to change.